The Effect of Using Hello English Application System on the Students’ Speaking Skill - Putri Handayani; Zulfitri (Merwin Publisher, 2023)
This research aims to determine whether there is a significant influence of the use of digital systems on the speaking skills of students in ten grade Senior High School. This research is a quantitative with anexperimental design. It was conducted in ten grade SMK NEGERI 1 BERINGIN under the academic year 2020/2021. The total population was 168 students and researchers took 20 students for the experimental class and 20 students for the control class which meant 40 students as a total sample. In collecting data, researchers used speaking test. Tests are pre-tests given before treatment and post tests given after treatment. Then, the data obtained were analyzed using t-test at SPSS 20 with a significance level of 5% (0.05). Furthermore, the t-test resultsshowed that t-test (3.327) was higher than t-table at a significance level of 5% (0.05) with a degree of freedom 38 being 2.024. Therefore, the results of t-test>t-table result that H0 (null hypothesis) is rejected and Ha (alternative hypothesis) is accepted.Thus, the Hello English application has a significant influence on students' speaking skills in ten grade SMK NEGERI 1 BERINGIN.